1990
DOI: 10.1056/nejm199007123230205
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Heavy-Charged-Particle Bragg-Peak Radiation for Intracranial Arteriovenous Malformations

Abstract: Given the natural history of these inaccessible lesions and the high risks of surgery, we conclude that heavy-charged-particle radiation is an effective therapy for symptomatic, surgically inaccessible intracranial arteriovenous malformations. The current procedure has two disadvantages: a prolonged latency period before complete obliteration of the vascular lesion and a small risk of serious neurologic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
0
7

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(157 citation statements)
references
References 18 publications
4
146
0
7
Order By: Relevance
“…Previous studies on intracranial AVMs have reported that the risk of hemorrhage during the latency period decrease [37][38], remains unchanged [36,39], or even increases [15,40] when compared with the natural course of the disease. Of note, these prior cerebral AVM studies tended to compare the risk of hemorrhage among selected patients who underwent radiosurgery with patients who did not undergo radiosurgery; in contrast, the present series analyzed changes in the rate of hemorrhage pre-and post-radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on intracranial AVMs have reported that the risk of hemorrhage during the latency period decrease [37][38], remains unchanged [36,39], or even increases [15,40] when compared with the natural course of the disease. Of note, these prior cerebral AVM studies tended to compare the risk of hemorrhage among selected patients who underwent radiosurgery with patients who did not undergo radiosurgery; in contrast, the present series analyzed changes in the rate of hemorrhage pre-and post-radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of radiation dose throughout this series was the product of a complex calculus that drew upon an extensive radiosurgical experience with cerebral AVMs in critical deep brain regions [15], and later on, a growing understanding of the risks and benefits of using different doses to manage a range of intra-and extra-axial vascular and non-vascular spinal lesions [16]. At the initiation of this study, there was no prior experience with treating spinal lesions with radiosurgery.…”
Section: Radiosurgical Dosagementioning
confidence: 99%
“…Lunsford et al 7 stated that 16% of the 207 patients they treated needed mild analgesia to control postoperative headaches. Steinberg and colleagues, 8 documented 40 patients with preoperative headaches. Twenty-seven percent exhibited no change after surgery, while 5% had worsening of symptoms.…”
Section: Commentsmentioning
confidence: 99%
“…2 All current studies relate AVM obliteration with relief of presurgical headaches. 2,4 Steinberg et al 8 proposed that after the collapse of the AVM nidus there is an improvement in regional cerebral blood flow, or normalization of hemodynamics. Coffey and associates 5 documented that 71% of AVMs which were greater than 10 cm 3 needed between 2 to 3 years before complete angiographic obliteration.…”
Section: Commentsmentioning
confidence: 99%
“…At the University of California at Berkeley -Lawrence Berkeley Laboratory (UCB-LBL) we have. developed stereotactic heavy-charged-particle Bragg peak radiosurgery for treatment of symptomatic surgicallyinaccessible intracranial arteriovenous malformations (AVMs) [1][2][3][4][5][6][7][8][9][10]. Narrow beams of accelerated helium ions are directed stereotactically to defined intracranial targets.…”
Section: Introductionmentioning
confidence: 99%